Sherlock Holmes : the complete novels and stories, Vol. 2 - Doyle, Arthur Conan (New York : Bantan, 1986)
National Theatre, direction: A.L. Erlanger & W.H. Rapley, business management, S.E. Cochran. Farewell to the stage. William Gillette, his last performance in the theatre in his famous creation of "Sherlock Holmes," being a hitherto unpublished episode in the career of the great detective and showing his connection with the strange case of Miss Faulkner, by William Gillette and Sir Arthur Conan Doyle, direction A.L. Erlanger and George C. Tyler. Play directed by William Postance, scenery designed and painted by Gates & Morange, constructed by Frank Dwyer, Inc., properties and furniture by William Bradley Studios, draperies by I. Weiss & Son, electrical effects by A. Greshoff, Miss Beatty's costumes by Dodd-Miller, Miss Entwistle's dresses by Maria Odio.
National Theatre [Washington, D.C.], week of January 6 to January 11, 1930. Matinee Saturday only.
Title devised by Library staff.
"The Playgoer, a magazine in the theatre. Vol. 1, no. 17, Jan. 5, 1930 to Jan. 11, 1930"--p. 3.
Cast: William Gillette, Wallis Clark, Brinsley Shaw, Byron Russell, Alfred Ansel, John Miltern, Montague Shaw, William Postance, Harry Joyner, William H. Barwald, Herbert Wilson, Henry Lambert, Fred Tasker, Burford Hampden, Donald Campbell, Peg Entwistle, Dorothy Peabody Russell, Roberta Beatty, Kate Byron, Rose Kingston.
"Next week beginning Monday night, matinees Wednesday and Saturday, Geo. M. Cohan in 'Gambling'"--p. 3.
LC copy 1 accompanied by 4 p. illustrated brochure advertising "Farewell to the stage. William Gillette in his famous creation 'Sherlock Holmes'.".
Keywords: Holmes, Sherlock -- Drama; Theater programs -- Washington (D.C.); Theater programs -- 1930.